The Radical and Disruptive Entrepreneurial Innovation Culture in South Africa’s townships - Bramwell Kundishora Gavaza; Siphenathi Fihla; Regina Stofile (Research Synergy Foundation, 2025)
Entrepreneurial innovation culture equips entrepreneurs with essential business management skills while providing a broader understanding of societal and economic development factors. This study examined South African townships’ radical and disruptive entrepreneurial innovation culture. Entrepreneurial innovation culture leads to small businesses maintaining their competitive advantage in the market. Therefore, investigating the inclusion of concepts such as entrepreneurial radicalism and disruptive innovation as elements to the entrepreneurial innovation culture in South Africa’s townships can help South African township entrepreneurs and business practitioners formulate guidelines to regulate business operations in townships. The study was conducted using a qualitative research approach, and convenience and purposive sampling methods were used to collect data. The study was conducted with 30 participants who are small business owners in South African townships. The data were collected using five focus groups from the selected 30 participants. The results provided evidence of three factors influencing the township’s small business environment: disruptive technology, entrepreneurial culture, and entrepreneurial radicalism. Moreover, the findings indicated that the township entrepreneurs in South Africa have developed a unique way of conducting business that maintains a competitive edge and ensures business growth and profitability. The study concludes that using new entrepreneurial strategies and technology in small businesses significantly derives a radical and disruptive innovation culture in South African townships that is capable of maintaining a competitive edge and ensuring business growth and profitability